Holmes tremor following midbrain abscess in an immunocompromised patient: a case report - Izzuddin, Anas Aminin W.M.; Khan, Abdul Hanif Khan Yusof; Apandi, Laila Mastura Ahmad; Loh, Wei Chao; Chia, Peck Kee; Mat, Liyana Najwa Inche; Sulaiman, Wan Aliaa Wan; Hoo, Fan Kee; Basri, Hamidon (Wolters Kluwer Medknow Publications, 2026)
Holmes tremor (HT) is a rare occurrence due to insults located at the midbrain. We are reporting a case of HT, which occurred in a retroviral disease patient who presented with a 1-week history of fever associated with third and fourth cranial nerve palsy. Magnetic resonance imaging of the brain revealed a midbrain lesion favoring abscess with blood investigations revealed positive serology for toxoplasmosis. The patient was started on toxoplasmosis treatment coupled with a six-week course of antibiotics. Following one-month post-treatment, the patient complained of a tremor that characteristics of HT with repeated computed tomography brain revealed resolving brain abscess. This case highlights an important reminder of potential neurological sequelae due to midbrain abscess and the importance of recognition of HT. The management of HT is challenging, involving the initial use of dopaminergic agonists with a potential role of deep brain stimulation in refractory cases.